2012
DOI: 10.1039/c2mt20139a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ni-(l-His)2 as a substrate for NikABCDE-dependent nickel uptake in Escherichia coli

Abstract: Nickel is an important cofactor for several microbial enzymes. The ATP-dependent NikABCDE transporter is one of several types of uptake pathways known to be important for nickel acquisition in microbes. The Escherichia coli NikA periplasmic binding protein is structurally homologous to the di- and oligopeptide binding proteins, DppA and OppA. This structural similarity raises interesting questions regarding the evolutionary relationships between the recognition of nickel ions and short peptides. We find that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Moreover, this trace nickel is thought to be predominantly bound by host-derived ligands (15,16). Indeed, the NikA substrate is not free nickel Ni(II) but rather a Ni-(L-histidine)2 complex (17). The ability of Ybt, another nitrogen heterocycle, to form nickel complexes raises the question of whether Ybt facilitates nutritional nickel uptake in uropathogenic E. coli.…”
mentioning
confidence: 99%
“…Moreover, this trace nickel is thought to be predominantly bound by host-derived ligands (15,16). Indeed, the NikA substrate is not free nickel Ni(II) but rather a Ni-(L-histidine)2 complex (17). The ability of Ybt, another nitrogen heterocycle, to form nickel complexes raises the question of whether Ybt facilitates nutritional nickel uptake in uropathogenic E. coli.…”
mentioning
confidence: 99%
“…A recent study has shown that NikA binds a (L-His) 2 Ni complex, and that Ni(II) and L-His are likely co-transported through the E. coli NikABCDE system. 18 The presence of a similar complex has been demonstrated for the periplasmic binding protein CeuE in H. pylori. 19 It has been hypothesized that the presence of nickel complexes could occur in other systems.…”
Section: Introductionmentioning
confidence: 63%
“…Efficiency of the NikABCDE-dependent Ni transport in E. coli cells increases when Ni is complexed with (L-His) 2 . 18 Consistently, the crystal structure of the periplasmic nickel-binding protein NikA of E. coli in complex with Ni-(L-His) 2 has been subsequently described. 35 More recently, a similar crystal structure of the analogous CeuE periplasmic component that is supposed to be involved in nickel/cobalt acquisition together with the ABCtransporter components FecD/FecE in H. pylori has also been reported.…”
Section: Kinetics Of Nickel Transportmentioning
confidence: 89%
“…Experiments using wild-type and mutant E. coli strains showed that exogenous L-histidine was the best candidate for the nickel-complexing ligand. 17 No other molecule used, including polycarboxylic acids, provided even a modest fraction of the Ni(II)-uptake rate observed with L-His. The concentration dependence of Ni-uptake as well as binding to purified NikA both supported a ternary complex with a stoichiometry of Ni:2L-His:NikA.…”
Section: Abc-type Transportersmentioning
confidence: 99%
“…17,19 This transporter, initially annotated as Opp5A, has been shown to be important in S. aureus-linked urinary tract infections. 29 The…”
Section: S Aureus Nikamentioning
confidence: 99%